Medical abortion and manual vacuum aspiration for legal abortion protect women's health and reduce costs to the health system: findings from Colombia. Issue 44 (February 2015) - Rodriguez, Maria Isabel; Mendoza, Willis Simancas; Guerra-Palacio, Camilo; Guzman, Nelson Alvis; Tolosa, Jorge E
Abstract: The majority of abortions in Colombia continue to take place outside the formal health system under a range of conditions, with the majority of women obtaining misoprostol from a thriving black market for the drug and self-administering the medication. We conducted a cost analysis to compare the costs to the health system of three approaches to the provision of abortion care in Colombia: post-abortion care for complications of unsafe abortions, and for legal abortions in a health facility, misoprostol-only medical abortion and vacuum aspiration abortion. Hospital billing records from three institutions, two large maternity hospitals and one specialist reproductive health clinic, were analysed for procedure and complication rates, and costs by diagnosis. The majority of visits (94%) were to the two hospitals for post-abortion care; the other 6% were for legal abortions. Only one minor complication was found among the women having legal abortions, a complication rate of less than 1%. Among the women presenting for post-abortion care, 5% had complications during their treatment, mainly from infection or haemorrhage. Legal abortions were associated not only with far fewer complications for women, but also lower costs for the health system than for post-abortion care. We calculated based on our findings that for every 1, 000 women receiving post-abortion care instead of a legal abortion within the health system, 16 women experienced avoidable complications, and the health system spent US $48, 000 managing them. Increasing women's access to safe abortion care would not only reduce complications for women, but would also be a cost-saving strategy for the health system. Abstract : Résumé: La majorité des avortements en Colombie se déroulent encore hors du système de santé formel, dans différentes circonstances. La plupart des femmes obtiennent le misoprostol sur un marché noir florissant et s'auto-administrent la médication. Nous avons comparé les coûts pour le système de santé de trois approches de la prestation de soins en matière d'avortement en Colombie : soins post-avortement pour les complications des avortements à risque, et pour les avortements légaux dans un centre de santé, avortement médicamenteux uniquement avec le misoprostol et avortement par aspiration. Les dossiers de facturation des soins hospitaliers de trois institutions, deux grandes maternités et un dispensaire spécialisé en santé génésique, ont été analysés pour les procédures et taux de complications, et les coûts par diagnostic. La majorité des visites (94%) concernaient les deux hôpitaux pour des soins post-avortement ; les 6% restants se rapportaient à des avortements légaux. Seule une complication mineure a été observée parmi les femmes ayant subi un avortement légal, soit un taux de complication de moins de 1%. Parmi les femmes s'étant présentées pour des soins post-avortement, 5% avaient eu des complications pendant leur traitement, principalement dues à une infection ou une hémorragie. Les avortements légaux étaient associés avec un taux nettement inférieur de complications pour les femmes, mais aussi avec des coûts plus modiques pour le système de santé que les soins post-avortement. Sur la base de nos conclusions, nous avons calculé que sur 1000 femmes recevant des soins post-avortement au lieu d'un avortement légal au sein du système de santé, 16 présentaient des complications évitables et le système de santé dépensait $US 48 000 pour les prendre en charge. Élargir l'accès des femmes à des services d'avortement sûr réduirait les complications pour les femmes, mais serait aussi une stratégie de réduction des coûts pour le système de santé. Abstract : Resumen: La mayoría de los abortos en Colombia continúan ocurriendo fuera del sistema formal de salud bajo una variedad de condiciones, y la mayoría de las mujeres obtienen misoprostol de un floreciente mercado negro para el medicamento y se lo autoadministran. Realizamos un análisis de costos para comparar los costos del sistema de salud en tres estrategias para la prestación de servicios de aborto en Colombia: atención postaborto para las complicaciones de abortos inseguros; y para la interrupción legal del embarazo (ILE) en una unidad de salud, aborto con medicamentos inducido con misoprostol solo y aborto con aspiración por vacío. Se analizaron los registros hospitalarios de facturación de tres instituciones, dos maternidades importantes y una clínica especializada en salud reproductiva, con relación a los procedimientos y tasas de complicaciones, y costos por diagnóstico. La mayoría de las mujeres (el 94%) acudieron a los dos hospitales para recibir atención postaborto; el 6% fue para una ILE. Se encontró una sola complicación menor entre las mujeres que tuvieron una ILE, una tasa de complicaciones de menos del 1%. Entre las mujeres que acudieron en busca de atención postaborto, el 5% presentó complicaciones durante el tratamiento, principalmente infección o hemorragia. La ILE estaba asociada no solo con mucho menos complicaciones para las mujeres, sino también con menores costos para el sistema de salud, en comparación con la atención postaborto. Basándonos en nuestros hallazgos, calculamos que por cada 1000 mujeres que recibieron atención postaborto en vez de una ILE en el sistema de salud, 16 mujeres presentaron complicaciones evitables, y el sistema de salud gastó US $48, 000 manejándolas. Ampliar el acceso de las mujeres a los servicios de aborto seguro no solo reduciría las complicaciones para las mujeres, sino que también sería una estrategia de reducción de costos para el sistema de salud.